QUALITATIVE OPERATION INDICES OF TRANSPORT COMPLEX OF THE RUSSIAN FEDERATION - I. N. Pugachev; Yu. I. Kulikov; V. N. Sediukevich (Наука и техника)
The paper considers existing qualitative indices of transport services. Indices for evaluation of qualitative operation indices of transport complex have been proposed in the paper. Special attention has been devoted to interaction and coordination of various types of transport as the highest level of qualitative operation of transport complexes. Operational coordination of transport facilities is considered as introduction of modern management, information and communication systems while using satellite navigation-information systems. The paper has studied the possibility to create a modern automated management system for transport complex at the Ministry of Transport of the Russian Federation that ensures an efficient organization of standardized information exchange between transport complex participants.The paper provides efficient solutions on transport problems that lead to planned improvements of objective indices with small expenses. A special focus has been given to development of transport systems in large cities with the purpose to reveal their impact on operation of the national transport complex. The paper considers conceptual moments pertaining to designing and realization of an intellectual management system and creation of complex conditions that ensure maximally efficient transport management on city territory.The main purpose of transport infrastructure modernization in accordance with its types is to create modern efficient transport facilities and equipment for provision of technological infrastructure required for the system of objects included in the transport infrastructure. The modernization strategy must be governed by national policy in the field of any transport and in accordance with international development tendencies in transport industry and transport construction. In this respect the transport infrastructure is the very first consumer of innovative high technologies that determine scientific-andtechnological advance and competitive ability of national economy.